IMPLEMENTASI PROGRAM PEMBERIAN BANTUAN SOSIAL PENDIDIKAN DALAM RANGKA PEMBANGUNAN PENDIDIKAN DI PROVINSI RIAU - Wahyuni, Wella; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Providing social education assistance provided by the Riau Province government for students who cannot afford higher education costs, which are channeled through the Riau Province Regional Secretariat for People's Welfare Administration Bureau. This result can be seen from the still not optimal implementation carried out by the People's Welfare Administration Bureau. Researchers here discuss about education development policies in Riau Province (case study of providing social education assistance to students). The implementation of providing social education assistance has several problems in the distribution process at the People's Welfare Administration Bureau. The purpose of this study was to determine the implementation of educational development policies through the provision of educational assistance for students in Riau Province. This research uses a qualitative method using a phenomenological approach. This study uses the theory of Van Metter and Van Horn policy implementation in MeyziHeriyanto, Adianto and HasimAs'ari with indicators of policy size and objectives, policy sources, characteristics or characteristics of implementing agencies/agencies, communication between organizations related to activities implementing activities, implementing attitudes, and the economic, social and political environment. The results showed that the implementation of education development policies through the provision of social education assistance was not optimal. Because it is not in accordance with the criteria that are set and the stated objective ofthe policy, the lack of information from the government in the implementation of the provision of social education assistance to student applicants who took part in the process of implementation assistance, and the limited ability of the organization to carry out the tasks that had to be done in providing rocks. social education for underprivileged students in Riau Province.   Keywords: Policy, Educational Development, Education Socil Assistance